Extracorporeal membrane oxygenation (ECMO) in pediatric congenital heart disease: a comprehensive review - Muhammad Shaheer Bin Faheem; Hafiza Qurat Ul Ain; Muhammad Haroon-Ul-Rasheed; Rohma Aftab (The Egyptian Heart Journal)
Abstract Background Extracorporeal membrane oxygenation (ECMO), which provides life-saving assistance in severe cardiac and pulmonary failure cases, has emerged as an important technique in managing children with congenital heart disease (CHD). Main body In this review, we discuss the evolution of ECMO over the years, its clinical uses, and the results in pediatric CHD. ECMO has been utilized as a bridge to recovery, in stabilizing an individual after surgery, and as a bridge to heart transplantation. Cannulation procedures that are adjusted according to the anatomy of an individual have improved outcomes, although bleeding and neurologic concerns remain a matter of concern. In addition, long-term neurodevelopmental disorders and renal failure are also among the alarming outcomes. The use of newer anticoagulant drugs like bivalirudin, which lowers the risk of bleeding, and genomic testing for personalized treatment are examples of recent developments. Furthermore, neuroprotective techniques such as erythropoietin and dexmedetomidine can also enhance the neurocognitive outcomes. Finally, improvements in monitoring systems and pump technology contribute to increased ECMO efficacy and safety. Conclusion Despite these developments, ECMO’s expense and restricted accessibility remain major obstacles, especially in areas with low resources. In this review, the advancements in ECMO technology and care are highlighted, and it also emphasizes future research to address the current challenges.